The impact of social media on risk perceptions during COVID-19 in Saudi Arabia - Khadijah Angawi; Mutlaq Albugmi (Frontiers Media S.A., 2022)
BackgroundSocial media is considered a critical source for seeking health information, especially during outbreaks. During the Coronavirus disease 2019 (COVID-19) pandemic, social media played an important role in disseminating information. However, it has been a source of misinformation in many communities throughout the pandemic. Whether this disseminated information has a positive or negative impact, individuals' risk perceptions of disease are influenced. It is important to explore factors that build public behaviors and their adaptation of risk reduction measures during the COVID-19 pandemic. Therefore, the aim of this study is to determine the role of social media and its impact on the risk perceptions of the COVID-19 in Saudi Arabia.MethodsThis was a cross-sectional study, and participants were recruited using different social media outlets between August to October 2020. The survey was delivered through Qualtrics platform targeting Saudi Arabian residents over the age of 18 years old. The questionnaire was delivered in English and Arabic. A convenience sampling was used to recruit participants to the study. The survey link was posted on several social media platforms.ResultsA total of 2,680 respondents completed the online survey. The results showed that male gender, individuals earning 4,000-12,000 SAR, and employed had positive and significant relationships with risk perception compared to their counterparts (β: 0.044, p-value: 0.035 and β: 0.051, p-value: 0.041, β: 0.108 p-value: < 0.001, β: 0.119 p-value: < 0.001), respectively. In second block, individuals exposed to social media had higher risk perception (β: 0.096, p-value < 0.001). In third block, self-efficacy was significantly but negatively associated with risk perception, indicating individuals who were self-efficient were less likely to perceive risk for the COVID-19 (β: −0.096, p-value < 0.001). There was no interactive effect of social media and self-efficacy on risk perception.ConclusionThe current study results show that social media exposure to the COVID-19 information has a positive impact in shaping an individuals' risk perception. The study also suggests that there is a need for public officials and policymakers to develop effective communication strategies through risk communication campaigns targeted at women, individuals with lower socioeconomic status, and those who are single as they showed a negative relationship with risk perception.